Pathway Regulation of p63, a Director of Epithelial Cell Fate - Yoh, Kathryn; Prywes, Ron (Frontiers in Endocrinology, 2015)
The p53-related gene p63 is required for epithelial cell establishment and its expression is often altered in tumor cells. Great strides have been made in understanding the pathways and mechanisms that regulate p63 levels, such as the Wnt, Hedgehog, Notch and EGFR pathways. We discuss here the multiple signaling pathways that control p63 expression as well as transcription factors and post-transcriptional mechanisms that regulate p63 levels. While a unified picture has not emerged, it is clear that the fine-tuning of p63 has evolved to carefully control epithelial cell differentiation and fate.